Award of Public Contracts as a Means to Conferring State Aid: A Legal Analysis of the Interface Between Public Procurement Law and State Aid Law - Cecilie Fanøe Petersen (Copenhagen Business School (CBS), 2018)
The Thesis investigates the interface between State aid law and public procurement law with an emphasis on analysing when the award of public contracts by contracting authorities constitutes State aid within the meaning of Article 107(1) TFEU. Article 107(1) TFEU prohibits any aid granted by a Member State or through State resources in any form whatsoever which distorts or threatens to distort competition by favouring certain undertakings or the production of certain goods, in so far as it affects trade between Member States. Award of public contracts is governed by procedural rules laid down in the public procurement Directives which lay out specific rules and procedures for the award of public contracts. Furthermore, public contracts can – under specific circumstances – be awarded directly without the conduct of a tender procedure. These situations are referred to as legal direct award of contract. A contract can be legally awarded without the conduct of a tender procedure, e.g. when the value of the contract is below the thresholds set out in the Directives. Finally, situations might occur where the award of a contract directly to an economic operator falls under the scope of the procurement Directives and thus should have happened through a tender procedure. Such situations are referred to as illegal direct award of contracts. This Thesis analyses the extent to which State aid rules apply in the abovementioned situations.
hdl:10398/9614
Keywords: 650